Gender integration in food-system policies: an adapted policy assessment framework - Mawia, Harriet; Muchiri, Caroline; Frimpong-Wiafe, Belinda; Enahoro, Dolapo K. (CGIAR GENDER Impact Platform, 2025)
Food systems are complex and include multifaceted processes in food production, aggregation, processing, distribution, consumption and post-consumption disposal of food products. Ensuring gender equality within food systems is important because they connect various domains, such as health and nutrition, climate change, environment, fisheries, livestock and agriculture. This interconnectedness within food systems leads to significant implications for human health, including nutrition and diets, as well as climate and environment-related indicators. Interactions of gender within these domains complicate the equitable derivation and distribution of benefits from agricultural activities by women and men. Therefore, policies governing food systems in low- and middle-income countries need to integrate gender-responsive approaches into their design, implementation and monitoring, recognizing the multifaceted processes of food systems and how gender interacts with these processes. The existing tools and frameworks that assess gender integration within policies about food systems do not extend beyond the scope of agricultural production into other interacting domains. This working paper addresses this gap by developing an enhanced framework for evaluating gender integration in policy documents within and beyond agriculture. The thematic reach of this framework includes agriculture, livestock, fisheries, climate change, health and nutrition, environment, and natural resource management. By leveraging a gender and food-systems framework that deconstructs food-systems functions, and how they impact women and men differently, the framework offers structured guidance for incorporating gender-related considerations within policy documents relating to food systems. The framework also has implications for participatory policy processes—design, implementation and monitoring—that aim to foster gender-equitable benefits from food-systems interventions.